Velocity of Circulation of Goods - Lounsbury, Raymond H. (Quarterly Journal of Economics, 1933)
Journal Article Velocity of Circulation of Goods Get access Raymond H. Lounsbury Raymond H. Lounsbury University of Illinois Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 47, Issue 3, May 1933, Pages 545–547, https://doi.org/10.2307/1883985 Published: 01 May 1933